2020
DOI: 10.14744/eej.2020.44127
|View full text |Cite
|
Sign up to set email alerts
|

Histologic evaluation of artificial floors under MTA and Nano-filled resin-modified glass ionomer used to repair furcation perforation in dogs

Abstract: Objective: This study aimed to compare the tissue reaction of two repair materials for furcation perforations, nano-filled resin modified glass ionomer (Nano-FRMGI) and mineral trioxide aggregate (MTA), used with or without an artificial floor. Methods: A total of 96 teeth in 6 dogs were used for this study. After access cavities, root canals were prepared and obturated with gutta percha using cold lateral condensation technique. Perforations were then created on the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the present study we use beagle dogs as model for histopathological study of apical periodontitis due its anatomical and physiopathological similarities with humans. Experimental induction of apical periodontits in dogs teeth has being performed by histopathological studies for evaluation of new endodontic materials and modalities of treatment under the same operatory conditions applied in humans and with healing responses obtained in shorter periods than humans [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we use beagle dogs as model for histopathological study of apical periodontitis due its anatomical and physiopathological similarities with humans. Experimental induction of apical periodontits in dogs teeth has being performed by histopathological studies for evaluation of new endodontic materials and modalities of treatment under the same operatory conditions applied in humans and with healing responses obtained in shorter periods than humans [30].…”
Section: Discussionmentioning
confidence: 99%
“…Their protocols for outcome assessment differed in, for example, observation time points and outcome assessment methods. Many studies assessed these characteristics by means of scores (Aladimi et al, 2020; Al‐Daafas & Al‐Nazhan, 2007; Bakhtiar et al, 2017; Cardoso et al, 2018b; Noetzel et al, 2006; Samiee et al, 2010; Silva et al, 2019; de Sousa Reis et al, 2019) or cell counting (da Fonseca et al, 2019; Hassanien et al, 2015; Neto et al, 2010, 2012; da Silva et al, 2011; Silva et al, 2017; Tawfik et al, 2016). Even those studies that analysed the outcomes by means of scores evaluated different characteristics in each score.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the biological characteristics of repair materials, their extrusion to the surrounding tissues may compromise the success of furcal perforation repair (Al‐Daafas & Al‐Nazhan, 2007; Mente et al, 2010). Several studies evaluated the use of calcium sulphate as an artificial floor/barrier on the perforated floor to control placement and avoid material extrusion (Aladimi et al, 2020; Al‐Daafas & Al‐Nazhan, 2007; Bakhtiar et al, 2017; Neto et al, 2010, 2012). Most of these studies found that the addition of this barrier did not improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation